Great lessons in project management - Pratt, David, 1954- (Management Concepts Press, 2015)
Projects fail at an alarming rate, whether they are information technology, training, construction, or policy development projects. No matter the focus, each year we experience an abundance of challenged projects that either require super-human effort to resuscitate or die an untimely death. This book is a treasure trove of lessons learned from troubled projects and from projects that went well. This collection of stories describes the events surrounding a particular challenge a project manager faced or a tool that another used effectively. Managers of all types of projects can draw on these stories to validate their own good practices and to avoid the pitfalls so many have encountered on their projects. --